2008
DOI: 10.3184/030823408x303231
|View full text |Cite
|
Sign up to set email alerts
|

Novel heterocyclic compounds from 2-carboxy-6-methoxybenzofuran-3-acetic acid anhydride

Abstract: 2-Carboxy-6-methoxybenzofuran-3-acetic acid anhydride is utilised for the synthesis of novel polycyclic heteroaromatic compounds in which the benzofuran ring is fused or bound to pyrido [1,4]benzothiazine, thiazole, pyridine, pyrazolopyridine, pyrazole, pyrano-pyridine, and pyrazolo [1,5-a]pyrido[3,2-e]pyrimidines using versatile reaction strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It has also been found that the present procedure is applicable to the synthesis of not only isocoumarins but also their heteroaryl analogs . Thus, treatment of 1-methyl-1 H -indole-2-carboxylic acid ( 9a ) with 2a under conditions A′ (similar to conditions A in Table but in DMF) for 2 h gave 9-methyl-3,4-diphenylpyrano[3,4- b ]indol-1(9 H )-one ( 10a ) in 96% yield (entry 1 in Table ).…”
Section: Resultsmentioning
confidence: 85%
“…It has also been found that the present procedure is applicable to the synthesis of not only isocoumarins but also their heteroaryl analogs . Thus, treatment of 1-methyl-1 H -indole-2-carboxylic acid ( 9a ) with 2a under conditions A′ (similar to conditions A in Table but in DMF) for 2 h gave 9-methyl-3,4-diphenylpyrano[3,4- b ]indol-1(9 H )-one ( 10a ) in 96% yield (entry 1 in Table ).…”
Section: Resultsmentioning
confidence: 85%